2018
DOI: 10.1088/1741-4326/aac607
|View full text |Cite
|
Sign up to set email alerts
|

Free boundary 3D ideal MHD equilibrium calculations for non-linearly saturated current driven external kink modes in tokamaks

Abstract: It is shown that free boundary 3D equilibrium calculations in tokamak geometry are capable of capturing the physics of non-linearly saturated external kink modes for monotonic current and q profiles typical of standard (baseline) plasma scenarios. The VMEC ideal MHD equilibrium model exhibits strong flux surface corrugations of the plasma vacuum boundary, driven by the core current profile. A method is presented which conveniently extracts the amplitude of the corrugation in terms of Fourier components in stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Our collaboration has investigated the QH-mode both numerically and analytically. We have used the VMEC code to find saturated nonlinear MHD states [15]. These can be found in two regimes.…”
Section: Recent Work On Reactor Relevant Pedestalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our collaboration has investigated the QH-mode both numerically and analytically. We have used the VMEC code to find saturated nonlinear MHD states [15]. These can be found in two regimes.…”
Section: Recent Work On Reactor Relevant Pedestalsmentioning
confidence: 99%
“…Candidate modes which may explain the QH-mode are investigated using the VMEC [41] non-axisymmetric equilibrium code and the linear ballooning stability code COBRAVMEC [42,43]. Previous work has investigated how such a saturated MHD mode may appear at the plasma edge [15]. It has been shown that such a mode can appear due to the q profile being just below a rational value at the plasma edge.…”
Section: Vmec Equilibrium Modellingmentioning
confidence: 99%
“…Recent experimental findings point to the E × B shearing rate as the key ingredient for the development of the characteristics of these oscillations [19]. Indeed numerical investigations of QH-mode DIII-D plasma discharges with sheared E×B flows showed that low-n modes are linearly dominant and are eventually sustained in the nonlinear stage at moderately low amplitude [7,[20][21][22][23][24].…”
mentioning
confidence: 99%
“…While the characteristics of modes on the ballooning side in the NSTX discharges is very similar to ballooning modes in the known large aspect ratio cases, we will now focus on the difference of resistive PB modes in NSTX compared with the well known ideal peeling modes. Typical ideal kink-peeling modes in large aspect ratio have low toroidal mode number n and a rather narrow poloidal spectrum in straight field line coordinates as the perturbation wraps around the poloidal circumference [41,42]. To compare the properties of kink-peeling modes in NSTX and DIII-D, we choose DIII-D discharge 147105.…”
Section: Analysis Of Mode Eigenfunctionsmentioning
confidence: 99%